Partial contribution of rolling friction and drag force to total resistance of an elite wheelchair athlete - Barbosa, Tiago M. (2014)
In wheelchair racing, the main sources to loose energy are the rolling friction and the drag force. The aim of this research was to model the partial contribution of rolling friction and drag force to total resistance of an elite wheelchair athlete.